Productivity Rating Method for Labor Productivity Analysis of Packaging Pressing Section, Case Study at PT. X Kudus - Vera Amanda Putri; Richardus Widodo; Wahyu Kanti Dwi Cahyani (Fakultas Teknik Universitas 17 Agustus 1945 Surabaya, 2025)
Human resource or workforce management to achieve profits in a company can be seen from the level of productivity of its workers. The Productivity Rating method is one method used to measure the level of labor productivity. The measure obtained from this method is the Labor Utilization Rate (LUR), where productivity measurements are not only calculated from the time used for the main work (input), but in calculating productivity also involves the time of the work contribution carried out by each worker. In the Productivity Rating method, worker activities are classified into 3 things, namely Essential Contributory Work, Effective Work, and Ineffective Work. The purpose of the research is to analyze the productivity of the packaging pressing department workers at PT X Kudus using the Productivity Rating method. The productivity measure obtained from this analysis is the Labor Utilization Rate (LUR). The results of the productivity rating analysis show that overall the LUR at PT. X Kudus's pressing department is 57.27%, which means that workers in the pressing department are working productively, although in the LUR analysis there is still one worker who is not working productively.